Sedimentary processes and depositional environment of the distal part of the Bear Island Trough Mouth Fan, SW Barents Sea reconstructed from a giant piston core - Dahl, Nora (UiT Norges arktiske universitet, 2016)
Multi-proxy analyses of the giant piston core MD992301 (including lithostratigraphy, physical properties and XRF-scanning) and analyses of swath bathymetry data was integrated in order to reconstruct the glacial history and paleoenvironment of the distal parts of the INBIS channel, located between the distal Bear Island Trough Mouth Fan and Storfjorden Trough Mouth Fan. Based on the swath bathymetry data three main morphological features was identified. These features are interpreted to be upper slope gullies, debris lobes, and a larger channel identified as the INBIS channel and surrounding levees. Core MD992301 was divided into 14 lithological units based on lithology, grain size, physical properties and geochemical elements comprising sediments from ~166,000 – 0 cal yr BP. The main sedimentary processes was sedimentation from suspension settling, mass-transport deposits and ice rafting from icebergs and sea ice, which is interpreted to be the dominating sedimentary processes within the area. The main sources of sediment were the Barents Sea Ice Sheet. Based on their distribution, the gravity flow activity in the area was restricted to periods of large-scale glaciation of the Barents Sea continental shelf. The sedimentation rate was generally low, with the lowest values during interglacials. The estimated average sedimentation rate during LGM was estimated to be ~27.4 cm/kyr, and 5.5 cm/kyr during the present warm period, the Holocene. The Barents Sea Ice Sheet may to have reached the outer Barents Sea continental shelf up to four times during the deposition of the MD992301 sediments. During these large-scale glaciations, the INBIS channel is believed to have been an important conduit gravity flows towards the deep sea. The onset of mass-transport within the MD992301 is hence assumed to be directly related to the activity within the proximal INBIS channel. These intervals are found to be during Saalian (MIS 6), Early Weichselian (5d and 5b) and Late Weichsel (MIS 2), where there is an increase in the frequency ...